The Kauṣītaka Gṛhyasūtrānī = the Kaṣītaka Gṛhyasūtras with the commentary of Bhavatrāta - Śāmbavya (Panini Vaidika granthamala ;, 1982)
Aphoristic work, with commentary, on Hindu purificatory rites and domestic ceremonies, according to the Kauṣītaka school in Rgveda.